Beyond Persuasion: AI Risk of Manipulation in Research Recruitment. - Allen, William L. (American Journal of Bioethics, 2026)
This article examines the ethical concerns surrounding the use of artificial intelligence (AI) in recruiting participants for clinical research, focusing on the potential for AI-driven manipulation. It highlights how AI can exploit individual cognitive biases and emotional vulnerabilities more effectively and subtly than traditional methods, raising risks beyond accepted ethical standards. The article discusses "dark patterns"—design strategies that manipulate user behavior—and notes that current regulatory frameworks, including those by the FDA and Office of Human Research Protections, do not adequately address AI manipulation in research recruitment. It suggests limiting data collection and developing AI auditing tools as possible safeguards, while emphasizing the need for institutional review boards and research administrators to develop expertise in AI to mitigate manipulation risks amid shrinking regulatory oversight.